A.S. Byatt critical storytelling - Alfer, Alexa, 1968-; Edwards de Campos, Amy J.; ebrary, Inc. (Manchester ; New York : Manchester University Press : Distributed in the United States exclusively by Palgrave Macmillan, 2010)
This is a study of Byatt's fictional and non-fictional work. It provides contextualising commentary and devotes an entire chapter to Byatt's role as critic and public intellectual.
Includes bibliographical references (p. [157]-191) and index.
Electronic reproduction.
Keywords: Byatt, A. S. -- 1936- -- Criticism and interpretation; Electronic books